Bad Role Models? American Influence on Israeli Criminal Justice Policy - Aviram, Hadar (2021)
In this Article I rely on the public policy concept of policy transfer to examine the impact of U.S. legislation, litigation, and politics on the Israeli criminal justice landscape. The Article identifies four eras: 1. The Great Light from the West - the ascent of U.S. criminal justice as British influence fades; 2. The Decade of Rights - a misperception of America as a paragon of criminal justice rights and protections that results in influences on Israeli jurisprudence; 3. The Law-and-Order Enchantment Period - a time at which Israeli scholars and policymakers import punitive trends from the U.S., particularly in the area of innovation in policing and victims’ rights; and 4. The Era of Contention - a time at which Israeli scholars and policymakers bring with them critical perspectives on the U.S. and Israeli policy begins to question, and deviate from, its American counterpart. I conclude that changing patterns of elite networking can explain why Israel, initially in thrall to what it perceived as a paragon of civil rights, eventually parted ways with the U.S. as a source of influence: the emergence of a class of academics, public defenders, and policymakers educated in the U.S. and conversant in American criminological literature critical of the punitive turn and mass incarceration brought about informed critiques of the American model and led to a sobering up of the Israeli policymaking world. The Article proceeds to explain the relationship between the two countries through the framework of American Political Development. Following Malcolm Feeley's analysis, the Article finds that both countries – self-defining as developed – actually exhibit features of developing countries in the context of criminal justice: high levels of interpersonal violence and intolerance, a constant problem of police overreach, a legacy of racism and exclusion, high availability of weapons, and political corruption. This might explain Israel's fascination with American criminal justice not as an inspiration, but as cultural recognition of the similarities between the countries